Histological and Genotoxic Biomarkers in Prochilodus lacustris (Pisces, Prochilodontidae) for Environmental Assessment in a Protected Area in the Northeast of Brazil - de Lima Cardoso, Rayssa [UNESP]; Carvalho-Neta, Raimunda Nonata Fortes; de Castro, Antonio Carlos Leal; Ferreira, Cássia Fernanda Chagas; Silva, Marcelo Henrique Lopes; de Jesus Azevedo, James Werllen; Sobrinho, João Reis Salgado Costa; Santos, Débora Martins Silva (Springer Nature, 2018)
The quality of aquatic environments all around the world is being altered by different human activities that represent direct threat to the ecological system and the aquatic biota. This study aimed to evaluate the occurrence of histological and genotoxic alterations in Prochilodus lacustris as indicators of anthropic impacts in a lacustrine environment in northeast Brazil. The histological alterations were evaluated using the histological alteration index, and the genotoxic alterations were detected using the micronuclei test, at three sampling stations (S1, S2 and S3). The gills presented lesions with three stages of severity, with mild lesions more frequent in the specimens collected at station S1. Mild hepatic tissue lesions were the most frequent type in both areas. Micronucleus analysis showed that station S3 was the most affected. The biological responses observed indicated that the fish are under influence of environmental changes. It is important to highlight that the organisms collected at station S3 had a more compromised health status.
Keywords: Biomarkers; Gill; Histopathology; Liver; Micronuclei